Building capacity in urban schools: emphasizing partnerships between counselor education and elementary schools - Alexandra Frank; Dalena Dillman Taylor (Emerald Publishing, 2024)
Purpose - Post-COVID-19, public K-12 schools are still facing the consequences of the years of interrupted learning. Schools serving minoritized students are particularly at risk for facing challenges with academics, behavior and student social emotional health. The university counseling programs are in positions to build capacity in urban schools while also supporting counselors-in-training through service-learning opportunities. Design/methodology/approach - The following conceptual manuscript demonstrates how counselor education counseling programs and public schools can harness the capacity-building benefits of university-school partnerships. While prevalent in fields like special education, counselor educators have yet to heed the hall to participate in mutually beneficial partnership programs. Findings - Using the multi-tiered systems of support (MTSS) and the components of the university-school partnerships, counselor educators and school stakeholders can work together to support student mental health, school staff well-being and counselor-in-training competence. Originality/value - The benefits and opportunities within the university-school partnerships are well documented. However, few researchers have described a model to support partnerships between the university counseling programs and urban elementary schools. We provide a best practice model using the principles of university-school partnerships and a school's existing MTSS framework.